2013
DOI: 10.1068/a45186
|View full text |Cite
|
Sign up to set email alerts
|

Industries, Skills, and Human Capital: How Does Regional Size Affect Uneven Development?

Abstract: This paper addresses how the composition of industry structures, skills, and human capital is related to regional development in peripheral and central locations. We do this by means of ordinary least squares models to analyse the relationship between growth in purchasing power and employment growth between 2001 and 2008 as well as a selection of variables constructed via register data of the total population in Sweden. The analysis demonstrates an evident spatial division of postindustrial development that la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
(74 reference statements)
1
16
0
1
Order By: Relevance
“…Instead, our study indicates that it is only the largest and/or most diversified regions that enjoy stable job creation. In combination with a continuous dismantling of the manufacturing sectors and a further focus in policy circles on knowledge-intensive services -that tend to agglomerate in large regional centres due to localization economies and diversity of local markets (Eriksson and Hansen, 2013) -this may lead to a deepning of spatial divisions characterized by even greater regional disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our study indicates that it is only the largest and/or most diversified regions that enjoy stable job creation. In combination with a continuous dismantling of the manufacturing sectors and a further focus in policy circles on knowledge-intensive services -that tend to agglomerate in large regional centres due to localization economies and diversity of local markets (Eriksson and Hansen, 2013) -this may lead to a deepning of spatial divisions characterized by even greater regional disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Academic human capital is important for regional development, but the vast literature on innovation, learning, knowledge production and more recently industrial knowledge bases suggests that other forms of knowledge, and hence other labour capabilities or competences, have an impact on firm competitiveness, and in turn on regional development. Thus, it is also the composition of skills, including technical skills and the specific industrial structures, that matters for regional development (Eriksson & Hansen, 2013). For instance, Leiponen (2005) has demonstrated that, without sufficient skills, including technical skills, manufacturing firms in Finland benefitted less than they might have done from innovation because they did not have the necessary complementary capabilities or absorptive capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Scott (2008aScott ( , 2010 illustrated the impact of cognitive human capital (people who are paid to think) in US metropolitan areas, where the focus remains on the highly skilled. In their analysis of Swedish regions, Asheim and Hansen (2009) revealed how different knowledge bases have their own specific geography of human capital, while Eriksson and Hansen (2013) examined the impact of different skills on regional growth. Hansen et al (2014) indicated strong variation in the use of human capital among manufacturing industries depending on the level of technology and their location in space, in particular urbanisation matters for the use of the highly skilled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, focus has been on the role of high concentrations of human capital and creativity when it comes to explaining postindustrial location tendencies and why certain localities prosper while others do not [6][7][8]. However, recent contributions have shown that it is not the pure agglomeration of certain industries and skills that primarily drive development but rather the composition of knowledge at both the level of the region [9][10][11][12] and within the firm [13]. Framing the issue of the geography of talents is its impact on the economic structure of the city region as a whole.…”
Section: Introductionmentioning
confidence: 99%